Ultra sensitive measurement of dielectric current under pulsed stress conditions. Issue 11 (November 2015) - Helfmeier, Clemens; Beyreuther, Anne; Fox, Alexander; Boit, Christian
Abstract: In order to perform electrical analysis of dielectrics in integrated circuits, various techniques have been employed in the past. Many of these included the use of large test structures and long measurement times to characterize the dielectric. This work presents a new method that circumvents both of these limitations. Analyzing the leakage behavior of the dielectric by charge measurements allows to use small structures and perform measurements with very short characterization times. This reduces the destructive nature of dielectric I–V-characterization significantly. It allows analysis of intrinsic dielectric behavior from small structures. A dielectric is analyzed to show the applicability of this procedure. The new analysis method enables measurements beyond previously available parameter ranges. Highlights: Charge measurement used to characterize dielectric I–V behavior Reduced stress imposed on dielectric test structure Significantly reduced structure size compared to conventional method Useful to derive intrinsic material properties